Effect of Addition of Composite Filler Volume on Ganoderma Boninense Mushroom Against Tensile Strength, Modulus of Elasticity, and Filler Distribution - Rafiq Yanhar, Muhammad; Bakhori Nasution, Ahmad; Rahmah Sibuea, Siti; Haris Nasution, Abdul (International Journal of Engineering and Technology, 2018)
This study aims to determine the effect of increasing filler volume of ganoderma boninense mushroom on tensile strength, modulus of elasticity, and distribution of the reinforcing particles. The composite reinforcement particle volume varies from 5%, 10%, 15%, and 20%. The mushroom is soaked with NaOH solution for 1 hour to remove dirt and sap that can reduce the bonds between matrix and particles. After that the mushrooms are made into mesh 50-sized particles using a blender with a rotation of 28,000 rpm. From the test results it can be seen that the highest tensile strength of 23.21 MPa is in the composite with a filler volume of 5%. The addition of particle volume to 10% makes the tensile strength slightly decrease to 21.04 MPa. The addition of filler volume to 15% and 20% causes the tensile strength to decrease to 20.55 MPa and 19.68 MPa. From the test results it can be seen that the lowest modulus of elasticity is in the composite with a filler volume of 5%. The addition of particle volume to 10% makes the modulus of elasticity rise to 83.15 MPa. The addition of filler volume to 15% and 20% causes the modulus of elasticity to increase to 126.77 MPa and 159.10 MPa. This shows that the more presence of ganoderma fungi in the composite causes the composite to become more elastic, thereby increasing the modulus of elasticity and decreasing tensile strength. The results of SEM photos showed the spread of mushroom powder at a volume of 5%, 10%, and 15% less evenly distributed, while in the filler 20% saw the spread of powder quite evenly.Â Â